2009
DOI: 10.1016/j.apgeochem.2008.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Towards a consistent geochemical model for prediction of uranium(VI) removal from groundwater by ferrihydrite

Abstract: 2 Uranium(VI), which is often elevated in granitoidic groundwaters, is known to adsorb 3 strongly to iron (hydr)oxides under certain conditions. This process can be used in 4 water treatment to remove uranium(VI). To develop a consistent geochemical model 5 for uranium(VI) adsorption to ferrihydrite, batch experiments were performed and 6 previous data sets reviewed to optimize a set of surface complexation constants using 7 the three-plane CD-MUSIC model. To consider the effect of dissolved organic matter 8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…Uranium chemistry is complicated, Langmuir (1978) identified 42 different aqueous species in thermodynamic calculations. Complexes with dissolved organic matter (DOM) and Ca-uranyl carbonate complexes were not considered in the calculations, but have recently been shown to be crucial for U speciation in water (Bernhard et al, 1996(Bernhard et al, , 2001Fox et al, 2006;Gustafsson et al, 2009;Prat et al, 2009). DOM-UO 2 complexes have been considered in some previous studies, but mainly in connection with U transport in the subsurface environment (Artinger et al, 2002;Ranville et al, 2007;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Uranium chemistry is complicated, Langmuir (1978) identified 42 different aqueous species in thermodynamic calculations. Complexes with dissolved organic matter (DOM) and Ca-uranyl carbonate complexes were not considered in the calculations, but have recently been shown to be crucial for U speciation in water (Bernhard et al, 1996(Bernhard et al, , 2001Fox et al, 2006;Gustafsson et al, 2009;Prat et al, 2009). DOM-UO 2 complexes have been considered in some previous studies, but mainly in connection with U transport in the subsurface environment (Artinger et al, 2002;Ranville et al, 2007;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…showed that the contribution of inorganic phases in this mor layer is likely to be small 21 In this work we used the 3-plane CD-MUSIC model [13] using the surface charging 10 parameters of Gustafsson et al [33] In the model approach, singly coordinated ≡FeOH 11 groups are assumed to determine proton charging. The site density is set to 6.3 sites nm -2 12 using a molecular weight of ferrihydrite of 89 g/mol and a specific surface area of 750 13 m 2 /g.…”
mentioning
confidence: 99%
“…The implementation of the CD-MUSIC model for uranium(VI) [33] considered the 22 possible existence of surface site heterogeneity by dividing the sites into high-and low-23 affinity sites with 99 % and 1 % of the number of sites, respectively. This approach is 1 similar to the one Dzombak and Morel [14] used for the Diffuse Layer Model.…”
mentioning
confidence: 99%
“…Comparisons between speciation predictions and observations have been made for different metals in various types of natural systems (Butler et al 2009;Gustafsson et al 2009;Wällstedt et al 2010;Nystrand et al 2012). However, most of these studies have focused on the behaviour of limited number of metals, in acidic waters.…”
Section: Materials Mobilization Via Bank and Bed Erosion Undermentioning
confidence: 99%
“…Frequently used speciation models include WHAM (Tipping 1994), PHREEQC (Parkhurst and Appelo 1999) and Visual MINTEQ (Gustafsson et al 2009). Although these models have been shown to provide excellent representation of metal speciation in laboratory environments (e.g.…”
Section: Materials Mobilization Via Bank and Bed Erosion Undermentioning
confidence: 99%